A Comprehensive Review of Lehana in Kaumarbhritya (AYUSHDHARA, 2025)
Lehana, a unique Ayurvedic practice described in the Kashyapa Samhita, involves the administration of lickable, semi-solid herbal formulations to infants and children to promote growth, immunity, intellect and overall health. As a cornerstone of Kaumarbhritya, the Ayurvedic branch dedicated to paediatrics, Lehana serves both preventive and therapeutic purposes. Traditionally initiated after Stanyapana (breastfeeding), Lehana involves the administration of medicated preparations such as Ghrita, Madhu, and herbal compounds tailored to the child's age, strength, and digestive capacity. Formulations such as Swarna Prashana, often include ingredients like honey, ghee and gold, aimed to enhance memory and work as an immunomodulator. This review explores the concept, formulations, indications, contraindications, and practical applications of Lehana in modern paediatric care. By analysing classical texts and contemporary research, this article highlights Lehana's relevance in addressing common ailments in children and enhancing developmental outcomes. The integration of Lehana into daily clinical practice offers a natural, palatable, and effective approach to paediatric healthcare, bridging traditional wisdom with modern needs.